Incentive-based Intervention to Maintain Breastfeeding Among Low-income Puerto Rican Mothers - Washio, Yukiko (Pediatrics, 2017)
BACKGROUND AND OBJECTIVE: Despite maternal and child health benefits, breastfeeding rates are relatively low among low-income Puerto Rican mothers. This study examined the hypothesis that monthly financial incentives would significantly increase the proportion of breastfeeding mothers at 6 months postpartum compared with Supplemental Nutrition Program for Women, Infants, and Children (WIC) services only among Puerto Rican mothers. METHODS: A randomized, 2-arm parallel-group design, from February 2015 through February 2016. Half of the randomized participants received monthly financial incentives contingent on observed breastfeeding for 6 months (Incentive), and the other half received usual WIC services only (Control). Thirty-six self-identified Puerto Rican women who initiated breastfeeding were enrolled. Monthly cash incentives were contingent on observed breastfeeding increasing the amount given at each month from $20 to $70 for a total possible of $270. RESULTS: The intent-to-treat analysis showed significantly higher percentages of breastfeeding mothers in the incentive group at each time point compared with those in the control group (89% vs 44%, P = .01 at 1 month; 89% vs 17%, P < .001 at 3 months; 72% vs 0%, P < .001 at 6 months). No significant differences were detected at any time point between study groups for self-reported exclusive breastfeeding rate and infant outcomes (ie, weight, emergency department visits). CONCLUSIONS: Contingent cash incentives significantly increased breastfeeding through 6-month postpartum among WIC-enrolled Puerto Rican mothers; however, no significant differences between the study groups were observed on exclusive breastfeeding rate and infant outcomes. Larger-scale studies are warranted to examine efficacy, implementation potential, and cost-effectiveness.